Water quality monitoring using lowcost digital camera / Ernieza Suhana Mokhtar - Mokhtar, Ernieza Suhana (2008)
Water quality describes the physical, chemical and biological characteristic of water that relates to human and nature life. Water quality parameters consist of Total Suspended Solids (TSS), turbidity, Secchi Disk Depth (SDD), temperature and colour. Example of factors affecting the quality of water bodies (i.e. lakes and reservoirs) are urban runoff, solid waste and soil erosion. Several methods i.e. conventional method, satellite remote sensing method, and digital camera method can be used to determine water quality parameters. Conventional method involves collecting water sample and laboratory analysis. This method is time consuming and not efficient to represent water quality of large area. Satellite remote sensing techniques using various sensors i.e. Landsat, Moderate Resolution Imaging Spectroradiometer (MODIS), IKONOS and Tiungsat-1 can be used to assess several water quality parameters (i.e. TSS, turbidity, chlorophyll and SDD) on large area coverage. Although this method can be used to monitor water quality of large area, image acquisition and data processing are costly and time consuming. A number of studies have utilized digital cameras to determine the water quality parameters; the results are still not conclusive. The aim of this study is to access the potential use of low-cost digital cameras in water quality assessment. Based on this aim, the objectives are i) to determine the relationship between digital number (DN) and TSS concentrations using different digital cameras; ii) to determine turbidity concentrations based on the calculated TSS values and iii) to compare TSS and turbidity concentration based on different models, different digital cameras and different dates of study area. The study areas for this research are two lakes located at Section 7 and Section 14 (Taman Tasik Shah Alam). This study only concentrates on two water quality parameters (i.e. TSS and turbidity). Two digital cameras (i.e. Olympus FE-100 and I-iC2070) each costing less than RM1000 were used to capture image of the water surface. The methodology adopted for this research involve i) collecting water samples, ii) capturing digital images of water surface, iii) data analysis (including regression analysis and generating water quality maps of the study area). Water samples collected in these two lakes were processed in the laboratory to determine the TSS and turbidity concentrations. Digital images captured on three different dates i.e. 1st and 15th September 2006 and 23rd November 2006 were used to determine the regression models (or relationship between DN and water quality concentration).